Interactive patient blood management dashboards used in Western Australia. Issue 12 (27th September 2016) - Trentino, Kevin M.; Swain, Stuart G.; Geelhoed, Gary C.; Daly, Frank F.S.; Leahy, Michael F.
Abstract : View Supplementary Video 1